2021
DOI: 10.1557/s43579-021-00034-y
|View full text |Cite
|
Sign up to set email alerts
|

Microbial repellence properties of engineered spider silk coatings prevent biofilm formation of opportunistic bacterial strains

Abstract: Bacterial infections are well recognised to be one of the most important current public health problems. Inhibiting adhesion of microbes on biomaterials is one approach for preventing inflammation. Coatings made of recombinant spider silk proteins based on the consensus sequence of Araneus diadematus dragline silk fibroin 4 have previously shown microbe-repellent properties. Concerning silicone implants, it has been further shown that spider silk coatings are effective in lowering the risk of capsular fibrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…It is a low-virulence opportunistic pathogen, which may cause a wide range of infections, often following surgery and in relation with the use of medical devices [ 88 ]. Cases of elbow joint and prosthetic joint infections, as well as post-operative discitis, have also been reported [ 89 , 90 , 91 , 92 ]. Corynebacterium vitaeruminis has already been proved to be safe and non-pathogenic; indeed, this strain was negative for 50 tested virulence and resistance genes based on performed PCR, according to Colombo et al [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is a low-virulence opportunistic pathogen, which may cause a wide range of infections, often following surgery and in relation with the use of medical devices [ 88 ]. Cases of elbow joint and prosthetic joint infections, as well as post-operative discitis, have also been reported [ 89 , 90 , 91 , 92 ]. Corynebacterium vitaeruminis has already been proved to be safe and non-pathogenic; indeed, this strain was negative for 50 tested virulence and resistance genes based on performed PCR, according to Colombo et al [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the recombinant spider silk protein coatings acted as a bioshield, improved the biocompatibility and significantly decreased the foreign body response to the implant [201,202]. Additionally, it was shown that coatings made of eADF4(C16) silk protein on silicone surfaces could also enhance microbe-repellent properties against four opportunistic infection-related strains, leading to reduced microbial adherence up to 99.7% in comparison to uncoated silicone surfaces [203]. Zhang et al reported a different repellent effect, due to triboelectric charging of a film made from recombinant spider silk proteins based on a MaSp1 sequence [204].…”
Section: Antiadhesive Propertiesmentioning
confidence: 99%
“…With regard to environmental factors, the advantages of these materials are apparent, as cellulose is derived from regrowing plant material, and microorganisms can produce recombinant spider silk proteins in large-scale bioreactors [ 5 ]. The excellent biocompatibility of cellulose [ 6 , 7 , 8 ], combined with the biocompatibility and shielding properties of recombinant spider silk [ 9 , 10 , 11 ] make these novel optical fibers a promising alternative for medical applications.…”
Section: Introductionmentioning
confidence: 99%